Out-of-Plane Shaking Table Tests on Seismic Response of RC Frame Infilled with a New Type of Shale Fired Heat-Insulation Blocks - Jian Wu; Li-dan Zhang; Qing Yu; Bo Wang (Advances in Materials Science and Engineering)
Shale fired heat-insulation block, which is made of shale, fly ash, building rubbish, and waste paper, is a new type environment-friendly product. In order to study the mechanical properties of shale fired heat-insulation block walls, four full-scale walls were tested under El-Centro, Taft, and Ninghe earthquakes using shaking table equipment, in which the influence of the spacing of cast-in-place belt and the connection between the wall and the frame on the out-of-plane seismic performance of the wall was taken into account. The subject of this study is mainly about out-of-plane dynamic response of masonry walls in terms of frequency, displacement, and acceleration. It could be concluded that the cast-in-place belt and the rigid connection between wall and RC frame could effectively reduce the out-of-plane seismic response of the infill masonry wall. Finally, the recommendations for the use of this type of block in the structure are given.